Synthesis, Structure-Activity Relationships, and Parasitological Profiling of Brussonol Derivatives as New Plasmodium falciparum Inhibitors - Camila S. Barbosa; Anees Ahmad; Sarah El Chamy Maluf; Igor M. R. Moura; Guilherme E. Souza; Giovanna A. H. Guerra; Roberto R. Moraes Barros; Marcos L. Gazarini; Anna C. C. Aguiar; Antonio C. B. Burtoloso; Rafael V. C. Guido (MDPI AG, 2022)
Malaria is a parasitic disease caused by protozoan parasites from the genus Plasmodium. Plasmodium falciparum is the most prevalent species worldwide and the causative agent of severe malaria. The spread of resistance to the currently available antimalarial therapy is a major concern. Therefore, it is imperative to discover and develop new antimalarial drugs, which not only treat the disease but also control the emerging resistance. Brussonol is an icetexane derivative and a member of a family of diterpenoids that have been isolated from several terrestrial plants. Here, the synthesis and antiplasmodial profiling of a series of brussonol derivatives are reported. The compounds showed inhibitory activities in the low micromolar range against a panel of sensitive and resistant P. falciparum strains (IC50s = 5-16 μM). Moreover, brussonol showed fast-acting in vitro inhibition and an additive inhibitory behavior when combined with the antimalarial artesunate (FICindex~1). The mode of action investigation indicated that brussonol increased the cytosolic calcium levels within the parasite. Hence, the discovery of brussonol as a new scaffold endowed with antiplasmodial activity will enable us to design derivatives with improved properties to deliver new lead candidates for malaria.